Pendekatan Perolehan Lahan sebagai Alternatif Mitigasi Banjir Surakarta - Muhammad Chrisna Satriagasa; Akhmad Makhfatih (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2019)
Surakarta City has experienced various losses due to flooding. Kali Pepe Catchment contributes to flooding that occurs in Surakarta City, mainly by upstream areas dominated by agricultural activities. Land acquisition in the upstream area of Kali Pepe Catchment for reforestation can reduce the river discharge into the downstream region of Surakarta City. This study aimed at 1) making delineation of land acquisition areas, 2) determining the amount of fair replacement value, 3) calculating the amount of river discharge reduction. Analysis of land capability using a geographic information system was used to determine the reforestation area. The fair replacement value was calculated based on the Indonesian Assessment Standard 306, by involving the physical replacement component and non-physical replacement. The amount of river discharge reduction of the Kali Pepe Catchment was calculated using a rational discharge model. The results showed that the delineation of 1.269,67 ha, which is the target of land acquisition in the upstream of the Kali Pepe Catchment, requires a replacement value of IDR 909 billion. This treatment reduced the river discharge by 139.263 lt/sec or 29.4%. River discharge reduction can be a solution in overcoming flooding problems in the downstream region of the Kali Pepe Catchment, Surakarta City.